Determination of High Content of Titanium in Ilmenite by Inductively Coupled Plasma-Optical Emission Spectrometry with Sodium Peroxide Alkali Fusion - ZHAO Xin; YAN Hui; YU Lian-ling; TANG Xing; LIU Zhao (Yankuang ceshi, 2020)
BACKGROUND The main types of ilmenite resources are ilmenite ore, ilmenite placer, and rutile ore. Ilmenite is a mineral that is difficult to be digested, and generally insoluble in nitric acid, hydrochloric acid or an aqua system. For high-grade ilmenite, even if the sample is dissolved by hydrochloric acid-nitric acid-hydrofluoric acid-perchloric acid mixture, titanium element is also easy to hydrolyze to form insoluble partial titanic acid precipitation, which often causes great difficulties in analysis. However, the traditional methods such as volumetric and spectrophotometry have the problems of long operation process, many steps and low efficiency. OBJECTIVES To improve the accuracy of the analysis of titanium in ilmenite and test efficiency by choosing the appropriate pretreatment combined with large-scale instrument analysis methods. METHODS Using 2.0g sodium peroxide as flux, the samples were melted in a corundum crucible at 700℃ for 15min. The resulted melts were soaked in hot water of 40-50℃, and then acidified with hydrochloric acid. The high content of titanium in the sample was determined by inductively coupled plasma-optical emission spectrometry (ICP-OES). The effect of the sodium matrix was eliminated by diluting the standard solution with a blank test solution. The sample was decomposed completely by optimizing the melting temperature and time. The salt content in the solution was reduced by optimizing the quality of sodium peroxide to ensure the stability of the determination. The spectral interference was eliminated by optimizing the spectral lines and using the background deduction method. RESULTS The detection limit of this method was 0.0035%, the analytical ranges were from 0.0066% to 62.50% (both were calculated by TiO2 content). The relative standard deviations (RSD, n=12) were 1.1%-2.1% and the relative errors were -1.69%-1.11%, which was verified by the national standard materials (GBW07839, GBW07841) of ilmenite. For actual sample analysis, the relative standard deviations of the method (RSD, n=12) were less than 4%. The analytical results were consistent, compared with the national standard method (ferric ammonium sulfate volumetric method). CONCLUSIONS This method is used to effectively solve the problems of incomplete digestion of ilmenite and easy hydrolysis of high content ilmenite, and achieve rapidly quantitative analysis of titanium content in different ilmenite samples by ICP-OES.